Bond characteristics of SFRP composites containing FRP core/anchors coated on geopolymer mortar. (1st April 2018) - Khalid, Hammad R.; Ha, S.K.; Park, S.M.; Wang, Zhen; Lee, H.K.
Abstract: The present study investigates the bending bond characteristics of novel hybrid sprayed fiber-reinforced polymer (SFRP) composites containing fiber core/anchors. Carbon or basalt fiber cores were embedded in SFRP composites as core reinforcements, and of which their ends were inserted into the beams to act as anchors. Four-point bending bond tests were conducted to characterize the bonding behavior of these hybrid SFRP composites in terms of enhancement of the ultimate bond strength ( τ u ) . The effects of the type and number of FRP core/anchors on τ u of SFRP-coated geopolymer mortar were investigated. Furthermore, geopolymer mortar was reinforced with 0.5 and 1.5 wt% of short steel fibers to study the effects of fibers on τ u, and their results were compared with the efficiency of hybrid SFRP composites. The test results revealed that the hybrid SFRP composites had significant effects on the bond strength, and their bonding performance was relatively better than the fiber-reinforcement in geopolymer mortar. About 46% and 37% increments were observed in τ u through the use of hybrid SFRP composites and steel fiber-reinforcement, respectively. The effective bond length ( L e ) of hybrid SFRP composites was approximately 39 mm.